Les construccions de relatiu col·loquials en català. - SEGURA LLOPES, CARLES (Scripta)
Prof. Joan Solà studied in depth the relative constructions in Catalan and raised quite a few questions about the operation and interpretation of these constructions, especially those corresponding to colloquial uses, clearly differentiated from those belonging to formal registers. In this paper we will try to contribute to the knowledge of colloquial relative constructions in Catalan using the Cognitive Construction Grammar as a theoretical basis. We will use the corpus called PARLARS, which will involve focusing on the colloquial uses of the Valencian variety, corresponding, in addition, to speakers of the older generations, who, as we know, still maintain a degree of exposure to quite low formal uses of Catalan (and also Spanish). Our objectives will be: a) to verify the extent of relative constructions in cultured speech; b) to establish the limits of the uses that best fit the colloquial syntactic structure, that is, the one that uses a depronominalized relativizer with or without resumptive elements; and c) to check if the constructions containing resumptives elements mark any semantic difference compared to those without them or if, simply, there is a mere alternation strictly linked to the formal or informal register.